Transcription: On the move - Forties, Robert A; Ma, Jie; Wang, Michelle D (eLife, 2013)
Single-molecule experiments have shed new light on the mechanisms responsible for the movement of RNA polymerase along DNA during transcription.
Keywords: RNA polymerase II; transcription elongation; Brownian ratchet; translocation; backtracking; optical tweezer